2009
DOI: 10.1111/j.1365-2982.2009.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal motility changes following spinal cord injury

Abstract: Spinal cord injury (SCI) is associated with severe autonomic dysfunction in both the acute and chronic phases. Upper gastrointestinal (GI) motor dysfunction has been previously reported in humans and rats. Gastric emptying (GE) of a solid meal--as measured by the [(13)C]-octanoic acid breath test--is delayed in the first 3 weeks after either spinal cord transection (SCT) or contusion (SCC) in rats. This is one of the main findings of a new paper by Qualls-Creekmore et al. in the current issue of this journal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
(87 reference statements)
0
9
0
1
Order By: Relevance
“…Patients with spinal cord injury (SCI) is associated with autonomic dysreflexia (Furusawa et al, 2011), serious upper and lower neurogenic bowel dysfunction (NBD) (Preziosi & Emmanuel, 2009;Gondim, de Oliveira, & Thomas, 2010). NBD after SCI was clinically manifested by abdominal distension, intractable constipation, prolonged defecation and faecal incontinence, which seriously affected the normal life of patients (Zhu & Liu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with spinal cord injury (SCI) is associated with autonomic dysreflexia (Furusawa et al, 2011), serious upper and lower neurogenic bowel dysfunction (NBD) (Preziosi & Emmanuel, 2009;Gondim, de Oliveira, & Thomas, 2010). NBD after SCI was clinically manifested by abdominal distension, intractable constipation, prolonged defecation and faecal incontinence, which seriously affected the normal life of patients (Zhu & Liu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several treatment options, such as cell transplant methods, are being researched to overcome the disabilities that result from SCI. Most preclinical animal studies are performed in rodent models of SCI [4,[7][8][9]. The spinal cord is a vital part of the central nervous system and is housed in the spine.…”
Section: Introductionmentioning
confidence: 99%
“…An area of concern in the SCI population is chronic gastrointestinal (GI) dysfunction with its associated complications. Prior studies in the SCI population have demonstrated an increased incidence of abnormalities in the upper gastrointestinal tract, including gastroesophageal reflux disease (GERD), esophageal disorders, and delayed gastric emptying . Motility disorders of the esophagus result in a disruption or weakening of peristalsis, causing difficulty in swallowing, regurgitation of food, GERD, and at times, a spasm‐like chest pain.…”
Section: Introductionmentioning
confidence: 99%